Implementation of Booking Performance Application Using Bootstrap Case Study in PT XYZ - Sansprayada, Arfan; Mariskhana, Kartika (Politeknik Ganesha Medan, 2019)
Abstract—The need for information system development in a company is a basic requirement that must be met by each company in order to run its business processes properly. This is the basic key in a company in order to provide maximum results to find as many profits or profits. Application development or requirements in the application also provide speed for employees to carry out their activities to work properly and optimally. The development of the era requires that companies must be productive and have innovations so that the business wheel of the company can run well. This is based on the development of technology that is so fast that it requires special expertise in its application. This research is expected to be able to help some problems that exist in a company. Where its application can make it easier for employees to carry out their respective duties and roles in order to maximize their potential. For companies, the application of this application can accommodate the company's business wheels so that they can be properly and correctly documented . Keywords : Systems, Information, Applications